Effect of high cholesterol diet and alpha-tocopherol supplementation on endoplasmic reticulum stress and apoptosis in hippocampus tissue - SÖZEN, AHMET ERDİ; KARTAL ÖZER, NESRİN (My University, 2022)
Objective: Neurodegenerative diseases are life-threatening disorders that occur when cells in peripheral nervous system or brain lose function over time and ultimately die. Our study aimed to establish a high cholesterol fed rabbit model to investigate the status of endoplasmic reticulum (ER) stress, proteasome activity and apoptosis as well as the beneficial role of α-tocopherol on hippocampus. Methods: Hypercholesterolemic rabbit model was established by feeding on 2% cholesterol diet for 8 weeks, and α-tocopherol supplementation was applied with intramuscular injections. Alterations of Grp78, Grp94, Bax, Bcl-2 and BACE1 levels in hippocampus tissue were determined by western blotting, while proteasome activity was measured by fluorometric detection. Results: Cholesterol containing diet for 8 weeks increased well-known parameters of ER stress and apoptosis, together with no chance in proteasome activity. On the other hand, α-tocopherol supplementation in rabbits fed two percent cholesterol containing diet significantly down-regulated certain ER stress and apoptosis parameters along with an increase in proteasome activity. Conclusion: Our results underline a novel function of α-tocopherol in reducing cholesterol induced ER stress and apoptosis by increasing proteasome activity in the hippocampus.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Hypercholesterolemia; Endoplasmic reticulum stress; Proteasome; Apoptosis; Hippocampus; UNFOLDED PROTEIN RESPONSE; VITAMIN-E; PARKINSONS-DISEASE; ALZHEIMERS-DISEASE; OXIDATIVE STRESS; FED RABBIT; RISK; MECHANISMS; PATHOLOGY; NEURONS